Utilizing Folklore to Enhance English Oral Skills of Junior High School Students - Binsasi, Mario Valderamo Aliandro; Bouk, Edmundus; Pale, Erlinda Sonya; Sulaiman, Eugelin; Semiun, Thresia Trivict (International Journal of English Education and Linguistics (IJoEEL), 2025)
This research aimed to enhance the speaking skills of the third-grade students at SMPN Kota Baru Kefamenanu through the use of folklore. The study employed a pre-experimental design, consisting of three stages: pre-test, treatment, and post-test. Initial findings from the pre-test showed that students had an average speaking skill score of 53.60%, classified as "average." After incorporating folklore as a treatment in the learning process, the post-test results indicated a significant improvement, with an average score increasing to 83%, categorizing students as "very good" (71-85). This demonstrates that folklore was effective in improving students' speaking skills, moving them from an average to an excellent level of proficiency. Additionally, a questionnaire was distributed to assess students' perceptions of using folklore as a learning tool. The results revealed that 83% of students either strongly agreed or agreed that folklore significantly aided in enhancing their speaking skills. These findings suggest that folklore not only improves students' speaking abilities but is also well-received as an engaging and effective instructional method. This research provides insights into the benefits of integrating cultural narratives into language learning, contributing to more effective communication skills development.